Salt iodisation of processed foods in Germany: evidence, processors' perceptions and implications for public health - Katharina Bissinger; Roland Herrmann; Irmgard Jordan (British Food Journal, 2022)
Purpose: We provide primary data on salt iodisation of processed foods in Germany, analyse reasons for food processors' use or non-use of iodisation and derive implications for public health. Design/methodology/approach: Statistical evidence is presented on the use of iodised salt in bread and bakery products, meat and meat products and dairy products in the German grocery-retailing sector. Information is based on mobile data collection in a representative sample of grocery stores in four German cities. These data are analysed with logistic regression models. Additionally, an online survey of bakers and butchers is utilised to record and to explain the use of iodised salt in specialised food stores. Findings: Salt was added in 69.3% of the 29,910 foods analysed in the market study. When salt was added, iodised salt was used in only 28.5% of the cases. According to the online survey, only 44% of the bakers and butchers used iodised salt, and the user share declined over time. Incomplete information from processors on the role of iodised salt for public health is contributing to the low and declining user share. Originality/value: We combine different market research methods and elaborate that the recommendation by the German Federal Ministry of Food and Agriculture - "If salt, then iodised salt" - is implemented to a very limited extent by the food industry and specialised food stores. From the behaviour of food processors and their perceptions of salt iodisation we gain new insights for policy and public health.
Keywords: 330; Salt iodisation; Processed foods; Market research methods; Food retailing; Germany